Modelling the effect of wind resistance in the 200-m Sprint - Quinn, M. D. (International Journal of Computer Science in Sport, 2004)
A mathematical model is used to simulate the effect of wind conditions on men's and women's 200-m times. Four questions are posed: What is the effect of constant winds on 200-m performance? What is the effect of varying wind speed and direction? What is the effect of the lane allocation? How do wind conditions affect the velocity profile? The race is simulated for winds with constant velocity and direction, for winds from a constant direction where the velocity changes linearly or as a sinusoidal wave, and for winds of constant velocity with a continuously varying direction. Of interest are the different wind conditions which produce tail winds of 2m/s, the maximum allowable for records. Simulations show that prevailing conditions produce large differences in the time corrections. The difference between performances with a wind reading of +2 m/s, but very different conditions, can be 0.8s (men) and 1.0s (women). These are larger than previous estimates and make performance comparisons impossible. Simulations also show that a tail wind blowing directly down the straight exaggerates the difference in lane allocation. The model estimates that on a standard track, a 5m/s tail wind can produce a difference of 0.3s between lanes 1 and 8.